-(3y+1)-(-2y-3)=-5

Simple and best practice solution for -(3y+1)-(-2y-3)=-5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(3y+1)-(-2y-3)=-5 equation:


Simplifying
-1(3y + 1) + -1(-2y + -3) = -5

Reorder the terms:
-1(1 + 3y) + -1(-2y + -3) = -5
(1 * -1 + 3y * -1) + -1(-2y + -3) = -5
(-1 + -3y) + -1(-2y + -3) = -5

Reorder the terms:
-1 + -3y + -1(-3 + -2y) = -5
-1 + -3y + (-3 * -1 + -2y * -1) = -5
-1 + -3y + (3 + 2y) = -5

Reorder the terms:
-1 + 3 + -3y + 2y = -5

Combine like terms: -1 + 3 = 2
2 + -3y + 2y = -5

Combine like terms: -3y + 2y = -1y
2 + -1y = -5

Solving
2 + -1y = -5

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-2' to each side of the equation.
2 + -2 + -1y = -5 + -2

Combine like terms: 2 + -2 = 0
0 + -1y = -5 + -2
-1y = -5 + -2

Combine like terms: -5 + -2 = -7
-1y = -7

Divide each side by '-1'.
y = 7

Simplifying
y = 7

See similar equations:

| 25m+15+14m=25 | | 10.1+0.45(x+12)=6.244 | | 3+2r-2=8r+25-3r | | x^2+3x-8=2 | | 3x+4(8)=8 | | 2.75+22=134.75 | | ln(11)=ln(6x^2-10)-ln(x) | | 4p+5p=45 | | 3x^3y+15x^2y-6xy= | | p+p+28+2p-33=690 | | (5x-6y)(5x+6y)= | | 0=-16x^2+44x+6 | | 7.25c+5.50c=105.50 | | 8.6-2.2v=-5.3 | | (5x+6)(2x^2-9x+7)=0 | | x/9+x/2=11/18 | | 30+60v= | | -8(3b+1)+(25b-7)=0 | | y^3+12y^2+36y=0 | | .875p-.25=.5p | | 2n/3-6/7=24/21 | | 5.8q-1.2-5.1q=-0.3q-5.7 | | 9y+8=11y+5 | | 20(2x+6)=5(2-x)+2x | | x/3-4=-7 | | -(8y+2)-(-7y-5)=3 | | 7-56b= | | -7y+1=-8y+9 | | 6x+2y-12=0 | | 7+48n= | | 2(2x+2)=5x | | 7-48n= |

Equations solver categories